Evaluating Non-STEM Students' Understanding of Evolution: Basis for Designing Pedagogical Intervention - Jastine Kent Florungco; Dennis Caballes (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo, 2021)
Teaching human evolution, for it to yield fruitful results, should be initialized by understanding the perspective of the learners. This study was conducted to aid in achieving that objective, and also to provide ways for educators to come up with strategies that can be perceived and appreciated by learners, particularly those who are not inclined with science. The majority of the respondents are believers in the theory of human evolution. Most of the respondents expressed their belief that modern humans are successors of ape-like organisms. The majority of the same set of informants mentioned their need for clarity about the stages that humans underwent during the course of history, while almost all of those respondents stated that the utilization of various graphic materials to elucidate these evolutionary concepts. It was recommended that educators engage in learning methods that call the attention and those that can be easily understood by the students